2012
DOI: 10.5120/5649-8007
|View full text |Cite
|
Sign up to set email alerts
|

LCC Decision tree analysis using ID3

Abstract: The basic principle of soil and water conservation is to use the land according to its capability. Therefore the knowledge of land capability classification is a prerequisite and important for planning of watershed development programme. The capability of land depends upon the characteristics of the land like slope, soil depth and soil type. Considering this input parameters Land Capability Classification (LCC) decision tree is formulated using ID3 algorithm. Results shown by generated decision tree are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A detailed review of DT applications in agricultural and biological engineering may be found in [5] and [7]. In the field of applying DT algorithms for soil survey data, [15] evaluated ID3 DT for LCC with 12 simulated samples with soil depth, slope, and texture as attributes for LCC; however, model was not validated. ID3 DT algorithm was applied on soil survey data with an accuracy of 86.84% on 10-fold cross validation [16].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of DT applications in agricultural and biological engineering may be found in [5] and [7]. In the field of applying DT algorithms for soil survey data, [15] evaluated ID3 DT for LCC with 12 simulated samples with soil depth, slope, and texture as attributes for LCC; however, model was not validated. ID3 DT algorithm was applied on soil survey data with an accuracy of 86.84% on 10-fold cross validation [16].…”
Section: Introductionmentioning
confidence: 99%